The Influence of Problem Based Learning Models in Elementary Schools on Social Studies Subjects - Wahyunengsih Wahyunengsih; Anindah Sipa Lestari; Fitria Difa Nuzula; Imelda Suryati Maulani; Indah Listiana (CV. ULIL ALBAB CORP, 2024)
This research investigates the use of the Problem-Based Learning (PBL) method to improve student achievement in social studies learning in elementary schools. The PBL method is a student- centered learning approach where they learn through solving real problems. In this study, qualitative methods were used, including interviews and descriptive questionnaires with teachers. The research results show that PBL improves student learning outcomes, critical thinking skills, analytical skills, and problem solving abilities. Increasing student achievement is one of the main findings of this research. Students who are involved in learning using the PBL method show a better understanding of the subject matter and are able to apply their knowledge in real situations. Apart from that, students' critical thinking skills also experienced significant improvement. They become better able to evaluate information critically and make decisions based on in-depth analysis. Student motivation also increases as a result of implementing the PBL method. Students become more enthusiastic and motivated to learn because they feel more involved and have an active role in the learning process. PBL also contributes to improving the quality of student behavior and education, creating a more positive and productive learning environment. Overall, this study concludes that the PBL method is an effective strategy for social learning studies in elementary schools. By improving learning outcomes, critical thinking skills, and student motivation, PBL can help create a more meaningful and sustainable learning experience for elementary school students.